Efficiency Of Regional Development (Study For Establishing Regional Regulations In South Bolaang Mongondow Regency On Cooperation Between Local Governments) - GOBEL, Rahmat Teguh Santoso; MUHTAR, Mohamad Hidayat (Indonesia Strategic Sustainability, 2022)
Inter-regional cooperation is a system of working relationships carried out by two or more regions that are in a level and balanced position to achieve a common aim of enhancing people's welfare. South Bolaang Mongondow Regency's government is highly concerned about the significance of collaboration, both with neighboring regions, In this paper there 2 (two) research questions, namely; 1). What is the urgency of inter-regional cooperation in regional development?; 2). What are the philosophical, sociological and juridicial considerations for the information of a draft regional regulation on the implementation of Regional Coopertaion in South Bolaang Mongondow Regency?. The urgency of inter-regional cooperation found by the author is as follows; 1). Public Service Improvement; 2). Border Area; 3). Spatial Order 4).Disaster Management and Handling Potential Conflicts; 5). Poverty Reduction and Regional Disparities; 6). Increasing Role of Provinces; 7). Regional Expansion. And the Implementation of Regional Cooperation in South Bolaang Mongondow Regency required much deliberations and considerations in philosophical foundation, sociological foundation, and juridicial foundation. These considerations are as follows; a). Philosophical Foundation, The philosophical basis is a consideration or reason that demonstrates that the regulations formed base on Pancasila and 1945 Constitution; b). Sociological Foundation, Cooperation based on the needs and considerations of efficiency, effectiveness of public services and carried out in a mutually beneficial manner; c). Juridicial Foundation, The juridical or normative basis of a rule or rule, if the rule is part of a certain legal rule which in the legal rules points one to another.